PENGARUH ORIENTALISME DALAM PENDIDIKAN ISLAM DI INDONESIA - Evayatun Nimah (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
Orientalism is western society’s perpective to look at the eastern world. At the end, orientalism narrowed down to the study of Islamic religion. This paper aims to identify orientalism’s influences in Islamic education in Indonesia. The result of this study indicate that orientalism has positive and also negative effects. The positive effect is the development of Islamic literatures compiled by orientalists. The negative effect that Islamic teaching only prioritizes the ideology without discussing tolerance between religions.